2016
DOI: 10.1093/cercor/bhw141
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Structural Imaging Reveals Nonlinear Progression of Experience-Dependent Volume Changes in Human Motor Cortex

Abstract: Evidence for experience-dependent structural brain change in adult humans is accumulating. However, its time course is not well understood, as intervention studies typically consist of only 2 imaging sessions (before vs. after training). We acquired up to 18 structural magnetic resonance images over a 7-week period while 15 right-handed participants practiced left-hand writing and drawing. After 4 weeks, we observed increases in gray matter of both left and right primary motor cortices relative to a control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 77 publications
7
72
1
Order By: Relevance
“…A recent longitudinal study on healthy individuals showed that structural neuroplasticity was inversely quadratic over time, and that motor-cortex plasticity occurred without any significant change in functional responsivity within the same brain region (Wenger et al, 2016). This finding indicates that functional and structural changes may not always be linear, and similarly to the present thesis, also stress the importance of using multimodal neuroimaging techniques to elucidate neuroplasticity.…”
Section: Amygdala Neuroplasticity Is Time-dependentsupporting
confidence: 80%
“…A recent longitudinal study on healthy individuals showed that structural neuroplasticity was inversely quadratic over time, and that motor-cortex plasticity occurred without any significant change in functional responsivity within the same brain region (Wenger et al, 2016). This finding indicates that functional and structural changes may not always be linear, and similarly to the present thesis, also stress the importance of using multimodal neuroimaging techniques to elucidate neuroplasticity.…”
Section: Amygdala Neuroplasticity Is Time-dependentsupporting
confidence: 80%
“…These graphs allow one to assign properties to a node, and, in the context of dynamic networks during learning, one could imagine assigning properties to brain regions including activity magnitudes [122], oscillatory information [123], grey matter volumes [124], and dopamine levels [12] that together would offer a more comprehensive picture of the neurophysiological processes accompanying learning. Tools are currently being developed to extend the network metrics described earlier for use in annotated graphs.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…A great deal of research has been devoted to unveiling the functional changes at the basis of such improvements (Krakauer et al, 2019). At the neural level, neuroimaging ( e.g., Wiestler and Diedrichsen, 2013; Wenger et al, 2017; Yokoi and Diedrichsen, 2019) and transcranial magnetic stimulation (TMS) studies ( e.g., Rosenkranz et al, 2007; Reis et al, 2008; Mawase et al, 2017) have shown that training is accompanied by a plastic reorganization of the motor cortex, potentially supporting the formation of new motor memories. Most noticeably, training was shown to amplify resting corticospinal (CS) excitability ( e.g., Christiansen et al, 2018) and to induce learning-specific changes of motor activity during movement execution (Krakauer et al, 2004; Steele and Penhune, 2010; Shmuelof et al, 2014).…”
Section: Introductionmentioning
confidence: 99%